2015
DOI: 10.1016/j.jval.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Chronic Obstructive Pulmonary Disease Overlap Syndrome: Doubled Costs Compared with Patients with Asthma Alone

Abstract: Patients with asthma and COPD had nearly double the health care costs as did patients with asthma without COPD. The overall disease profile of patients with asthma should be considered when managing patients, rather than treating asthma as a solitary condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 22 publications
4
16
1
2
Order By: Relevance
“…Our findings of a greater comorbidity burden, medication use, and costs in the claims-positive ACO cohort compared with the claims-positive asthma and COPD cohorts were consistent with prior studies [18]. However, the lower costs observed in the confirmed ACO cohort differed from prior studies that showed ACO patients with higher resource utilization and costs [18,33-35].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings of a greater comorbidity burden, medication use, and costs in the claims-positive ACO cohort compared with the claims-positive asthma and COPD cohorts were consistent with prior studies [18]. However, the lower costs observed in the confirmed ACO cohort differed from prior studies that showed ACO patients with higher resource utilization and costs [18,33-35].…”
Section: Discussionsupporting
confidence: 87%
“…The literature suggests that, compared with asthma or COPD, ACO is associated with more rapid decline in lung function, more frequent exacerbations, increased health care resource utilization, worsening quality of life, and higher mortality rates [16,18,19]. This profile, however, relies on diversely defined populations and prevalence estimates [15,17,20] and might have dubious diagnostic utility.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of emergency room visits and intensive care unit admissions are higher among those patients with overlap syndrome compared to those with COPD but not asthma [12]. In addition, overall healthcare expenditure for patients with co-existent asthma and COPD is almost twice the expenditure for patients with asthma but not COPD [13].…”
Section: Reviewmentioning
confidence: 99%
“…2012-ben került publikálásra a spanyol konszenzusdokumentum az ACOS COPD-ben való szerepéről [13], illetve a 2015-ben publikált GINA (Global Initiative for Asthma) és GOLD (Global Initiative for Chronic Obstructive Lung Disease) dokumentumok is már tartalmaznak ajánláso-kat ezeknek a betegeknek az azonosításához [14]. További nem elhanyagolható szempont, hogy a betegség-hez kapcsolódó egészségügyi kiadások közel kétszer olyan magasak az ACOS-betegek esetében, mint az asthma vagy COPD önálló fennállása esetén [15,16]. Az 1. táblázatban foglaltuk össze azokat a kérdéseket, amelyek az ACOS fontosságának aktualitását mutatják meg.…”
Section: öSszefoglaló Közleményunclassified
“…A dokumentum kitér arra is, hogy a specifikus definícióhoz még további vizsgálatok szükségesek a kü-lönféle fenotípusok pontos meghatározásával. A légúti obstrukció igazolása után asthma, COPD, valamint való-színű asthma és valószínű COPD csoportok mellett lehet az ACOS klinikai diagnózisát felállítani [15].…”
Section: Definíció éS Diagnosztikai Megfontolásokunclassified